(untitled) (Journal of Leadership, Accountability and Ethics, 2020)
Corruption behavior has been difficult to both observe and measure despite its illegal nature and importance to firms and society both economically and politically. In empirical research, proxies for corruption are frequently generated. A popular proxy, as in Smith (2016), is corruption convictions. This study extends Smith’s analysis by examining data from 1998-2016, using Smith’s shielding and liquidity hypotheses. Through an updated and enhanced dataset, this study finds that the shielding hypothesis is supported for the sample; however, in the post-Citizens United subsample corruption convictions are not significant in various regressions. This study discusses the implications of the latter result and underscores the need for further research with a more comprehensive model to examine corruption in greater detail.